EFFECT ON THE QUALITY OF PUBLIC PERCEPTION IN HEALTH SEBULU KUTAI II - -, Elly Mustofa (EKONOMIA, 2015)
The problem of this study is whether the quality of service that consists of physical evidence, reliability, perception, assurance, and empathy, and physical evidence of a significant effect on public perception, and of the five variables in carefully which ones have the most dominant and significant influence on the perception community health centers Sebulu the Kutai II.The population of this research is public, while the sample is the smallest part of the population can be considered representative or representative of the overall respondents. In this study, researchers took 30 samples. Sampling technique using a nonprobability sampling technique is incidental. Where sampling is based on chance, ie, anyone who by chance met with researchers can be used as a sample when a person who happens to be encountered is considered suitable as a source of data.The data that have been collected in an analysis using multiple linear regression equation with SPSS 16.0 aids get the following results: Y = 1.473 + + + 0.196.X3 0.229.X2 0.440.X1 + + + 0.098.X5 0.129.X4. Based on the analysis and discussion, it can be concluded that the quality of services such as physical evidence, reliability, perception, assurance, and empathy significantly influence public perception.This is demonstrated by the results of the F test was significant (0.000 <0.05). Value of the correlation coefficient (R) of 0.851 means that there is a relationship together is stronger than the variable (X1) physical evidence, (X2) reliability, (X3) responsiveness, (X4) security, (X5) empathy towards public perception. Hypothesis is rejected there (X2) reliability, (X4) security, (X5) empathy) and accepted hypotheses (X1) physical evidence), (X3) responsiveness